BREAST CANCER ASSOCIATED ANTI YO-ANTIBODY MEDIATED PARANEOPLASTIC CEREBELLAR DEGENERATION: CASE SERIES AND REVIEW OF LITERATURE - Sanaullah Mudassir; Ashok Kumar; Neetu Sinha; Abhay Ranjan (MNJ (Malang Neurology Journal), 2022)
Paraneoplastic cerebellar degeneration (PCD) is a rare immune mediated disorder characterized by progressive cerebellar ataxia in presence of onconeural antibodies which occurs due to an indirect effect of underlying malignancy i.e. small cell lung cancer (SCLC), breast and gynecologic cancer, and Hodgkin lymphoma. In about 50% of patients neurological manifestation of Paraneoplastic cerebellar degeneration occurs prior to detection of carcinoma. Anti-Yo Antibody is the commonest antibody present in patients with Paraneoplastic cerebellar degeneration which is associated with breast carcinoma. We describe 3 female patients with anti YO antibody mediated PCD with breast cancer. One patient had a previous diagnosis of breast cancer with post mastectomy status one year back. Two of them presented with ataxia and on further examination, breast lump was found. All three patients had symmetrical ataxia with one patient had severely debilitating ataxia and was not able to walk unassisted. Magnetic resonance imaging brain showed cerebellar atrophy in two patients while one patient had normal MRI. Anti- YO antibody was strongly positive in all the three patients. All patients were given immunotherapy (corticosteroids in 2, Intravenous immunoglobulin in 1) with 1 patient showed modest improvement These case highlights the need to consider for workup for paraneoplastic cerebellar degeneration in female patients presenting with subacute to chronic progressive ataxia, so that the tumors can be detected and treated in early stage with a good outcome.